2015
DOI: 10.1161/circinterventions.114.002106
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Platelet Reactivity Over a Risk Score of Clinical and Procedural Variables in Predicting Bleeding After Percutaneous Coronary Intervention via the Femoral Approach

Abstract: Background-Growing evidence suggests that platelet reactivity (PR) may predict bleeding. We investigate the incremental value of PR in predicting bleeding after percutaneous coronary intervention (PCI) via the femoral approach over a validated bleeding risk score (BRS) of clinical and procedural variables. Methods and Results-A total of 800 patients undergoing elective PCI via the femoral approach were included. PR was measured before PCI with the VerifyNow P2Y12 assay and low PR was defined as a P2Y12 reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several clinical studies that have used the same assays have correlated platelet inhibition with bleeding risk. [34][35][36] In a literature review and expert consensus statement and in a large meta-analysis of 17 clinical trials that included more than 20,000 patients who were undergoing percutaneous coronary intervention and whose platelet function was measured with the use of a point-of-care P2Y 12 platelet-reactivity test or a VASP assay, low platelet reactivity was independently associated with an elevated bleeding risk. 37,38 In this trial involving volunteers who were pretreated with ticagrelor, low platelet reactivity was rapidly reversed by a new targeted monoclonal antibody fragment.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies that have used the same assays have correlated platelet inhibition with bleeding risk. [34][35][36] In a literature review and expert consensus statement and in a large meta-analysis of 17 clinical trials that included more than 20,000 patients who were undergoing percutaneous coronary intervention and whose platelet function was measured with the use of a point-of-care P2Y 12 platelet-reactivity test or a VASP assay, low platelet reactivity was independently associated with an elevated bleeding risk. 37,38 In this trial involving volunteers who were pretreated with ticagrelor, low platelet reactivity was rapidly reversed by a new targeted monoclonal antibody fragment.…”
Section: Discussionmentioning
confidence: 99%
“…After successful PCI, lower platelet reactivity on clopidogrel was an independent predictor of postdischarge bleeding, and these bleedings had a strong relationship with mortality at the 2‐year follow‐up point . Another recent study in a cohort of patients who underwent elective PCI suggested that LPR provided incremental predictive value for bleeding events through 30 days compared with a bleeding risk score . Although the influence of platelet reactivity on bleeding risk may differ for patients who undergo PCI versus ACS patients who are managed without revascularization, the primary 2‐level composite bleeding events in TRILOGY ACS occurred infrequently and were primarily spontaneous and unrelated to cardiovascular procedures.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another recent study in a cohort of patients who underwent elective PCI suggested that LPR provided incremental predictive value for bleeding events through 30 days compared with a bleeding risk score. 29 Although the influence of platelet reactivity on bleeding risk may differ for patients who undergo PCI versus ACS patients who are managed without revascularization, the primary 2-level composite bleeding events in TRILOGY ACS occurred infrequently and were primarily spontaneous and unrelated to cardiovascular procedures. The present analysis from TRILOGY ACS thus provides novel evidence for the relationship of platelet reactivity measurements with bleeding risk for ACS patients treated with DAPT who did not undergo PCI.…”
Section: Discussionmentioning
confidence: 99%
“…64 Similarly, Mangiacapra et al showed recently that a combination between platelet function testing results and a validated risk score of clinical and procedural variables yields significantly better prognostic performance than the clinical risk score or platelet reactivity on their own, emphasizing that there is a significant interaction between platelet reactivity and clinical variables. 65 These results are also important to understand failures of prior randomized studies of platelet function testing that generally enrolled very lowrisk patient populations both in terms of clinical risk profile and angiographic characteristics. 53,66…”
Section: Utilization Of Platelet Function Testing To Target the "Sweementioning
confidence: 99%